RCAN1 overexpression promotes age-dependent mitochondrial dysregulation related to neurodegeneration in Alzheimer’s disease - Wong, Helen (Acta Neuropathol, 2015)
Aging is the largest risk factor for Alzheimer’s disease (AD). Patients with Down syndrome (DS) develop symptoms consistent with early-onset AD, suggesting that overexpression of chromosome 21 genes such as Regulator of Calcineurin 1 (RCAN1) plays a role in AD pathogenesis. RCAN1 levels are increased in the brain of DS and AD patients but also in the human brain with normal aging. RCAN1 has been implicated in several neuronal functions, but whether its increased expression is correlative or causal in the aging-related progression of AD remains elusive. We show that brain-specific overexpression of the human RCAN1.1S isoform in mice promotes early age-dependent memory and synaptic plasticity deficits, tau pathology, and dysregulation of dynamin-related protein 1 (DRP1) activity associated with mitochondrial dysfunction and oxidative stress, reproducing key AD features. Based on these findings, we propose that chronic RCAN1 overexpression during aging alters DRP1-mediated mitochondrial fission and thus acts to promote AD-related progressive neurodegeneration.